1997
DOI: 10.1111/1468-5957.00138
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Selecting a Response Measure for Financial Distress

Abstract: Since 1966, researchers have examined financial distress prediction models to determine the usefulness of accounting information to lenders. These researchers primarily used legal bankruptcy as the response variable for economic financial distress, or included legal bankruptcy with other events in dichotomous prediction models. However, theoretical models of financial distress normally define financial distress as an economic event, the inability to pay debts when due (insolvency). This study uses a loan defau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 7 publications
1
27
0
4
Order By: Relevance
“…In the early days, the prediction of financial distress or bankruptcy often used financial ratios as the tool [1,[16][17][18]. Later, cash flow was also incorporated [19][20][21]. In recent years, corporate governance has been included as part of the equation for the prediction of financial crises or accounting fraud [3][4][5][6]10,11,[13][14][15]22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In the early days, the prediction of financial distress or bankruptcy often used financial ratios as the tool [1,[16][17][18]. Later, cash flow was also incorporated [19][20][21]. In recent years, corporate governance has been included as part of the equation for the prediction of financial crises or accounting fraud [3][4][5][6]10,11,[13][14][15]22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these issues, the research on the usefulness of cash flows in financial distress prediction produced somewhat mixed results. Many researchers indeed found that various cash flow-based ratios are statistically significant predictors of the forthcoming bankruptcy (Ohlson, 1980;Gentry et al, 1985;Casey and Bartczak, 1985;Ward and Foster, 1997;Bhandari and Iyer, 2013;Unegbu and Adefila, 2013;Khan and Guruli, 2015). However, Gupta et al (2012), in their study of British small and medium-sized enterprises, found that the presence of operating cash flow information does not improve the prediction accuracy of the distress prediction models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With such a use of EBITDA, the interest rate is often revised periodically, based on a grid of predetermined levels of the borrower's EBITDA-based ratios (Beatty et al, 2012;Beatty et al, 2015). EBITDA is also used in business valuation (Verninmen et al, 2005;Gray and Vogel, 2012;Hughen and Strauss, 2016), particularly of small private enterprises which do not report cash flow statement (Greenwald et al, 2001). The popularity of EBITDA is confirmed by a research, according to which EBITDA-based multiple is one of the two most frequently used valuation indicators by European stock analysts (Fernandez, 2002;Bancel and Mittoo, 2014;Lie and Lie, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investor trust will have a positive impact on the availability of working capital, while creditor confidence will impact on the decrease of cost of debt (Ashbaugh et.al, 2004;Byun, 2007;Bhojraj & Sengupta, 2003). Furthermore, Elloumi & Gueyie (2001); Supatmi (2007); Huang & Zhao, (2008); Fich & Slezak (2008); Ward & Foster (1997), Yin & Tsui (2004) and Sengupta & Faccio (2011) proved that the probability of financial difficulties of implementing GCG, is lower than companies that do not implement GCG.…”
Section: Introductionmentioning
confidence: 99%